Magneto-Optical Imbert–Fedorov Effect in Prism Coupling Configuration - Tingting Tang; Lei Bi; Li Luo; Jie Li; Yanfen Zhang; Ping Sun (IEEE Photonics Journal, 2017)
We study the Imbert–Fedorov (IF) effect in prism coupling configuration with magneto-optical (MO) material, which is called MOIF effect. An effective refractive index method MO waveguide is obtained based on the solution of Maxwell's equations. The expressions for IF and MOIF shifts are also derived. As left-handed circularly polarized (LHCP) and right-handed circularly polarized (RHCP) light beams have different effective refractive indices in MO waveguide when polar or longitudinal MO Kerr effects are taken into account, their IF shifts are asymmetric which are different from symmetric IF shifts in isotropic waveguides. By applying opposite magnetic field, a maximum MOIF shift close to 400 μm can be obtained with special waveguide configuration. MO effect will provide a new method to enhance and modulate the transverse shifts of LHCP and RHCP lights, which has not been considered up to now.